Cet obscur objet du désir… multiculturel (III) : ethnogenèse, ethnicisation et ethnification - Guillaume Boccara (Nuevo mundo - Mundos Nuevos, 2010)
The collective volume El Regreso del Indígena deals with the theoretical and practical problems linked to the implementation of multiculturalism in Latin America during the last 20 years. Starting by a critical reading of some of the articles of this book, we shall develop a reflection on the connections between multiculturalism and neoliberalism, the restructuring of the State, and the re-imagining of the Nation in the global era. We shall thus put into question the false alternative between particularism and universalism as well as between recognition and redistribution. We shall deal with the issues of ethnopolitics, racializing and contemporary ethnogenesis in a context characterized by the pervasiveness of neoliberal cultural patterns. We shall eventually examine the role and status of anthropological research in a context of ethnification and politicization of culture